Activation Markers of Coagulation and Fibrinolysis: Alterations and Predictive Value in Acute Coronary Syndromes - Hoffmeister, Hans Martin; Heller, Wolfgang; Seipel, Ludger (Thrombosis and Haemostasis, 1999)
Several alterations of the coagulation, of the fibrinolysis and of inflammation are known in patients with acute coronary syndromes. To extent current knowledge of the pathopysiology and to optimize therapeutical strategies, the new molecular markers can be used in clinical studies. Furthermore, several studies were undertaken to assess the prognostic value of activation markers of these systems for patients with unstable angina pectoris and acute myocardial infarction with or without thrombolytic therapy. The majority of studies focussed on markers of thrombin activation, fibrinogen, fibrin degradation products and t-PA and its main inhibitor PAI-1. While there are stimulating results from larger studies, the value for prognosis for the individual patient still is limited by the overlap of patients with good versus a poor outcome.
Keywords: Fibrinolysis; coagulation; inflammation; activation marker; acute coronary syndromes